Effect of the use of chestnuts in the finishing diet on fatty acid profile in different tissues of the Celta pig breed - Domínguez R.; Martínez S.; Franco I.; Carballo J. (7th International Symposium on the Mediterranean Pig, 2012)
The effect of the use of chestnuts in the finishing diet on the fatty acid profiles of different tissues (muscles and liver) of the Celta pig (an autochthonous breed from the NW of Spain) was studied. Thirty six pigs were separated in three different groups according to the type of feeding during the finish-fattening period (three months): commercial compound feed, mixture of the chestnuts and commercial compound feed, and chestnuts. Fatty acid composition of neutral (NL) and polar lipids (PL) in the intramuscular fat of Longissimus dorsi (LD) and Psoas maior and minor (PMM) muscles and in the hepatic fat were analysed. The predominantly oxidative PMM muscle had higher polyunsaturated and lower monounsaturated fatty acids contents than LD both in NL and PL. The oleic acid (C18:1 n-9) content in neutral lipids and linoleic (C18:2 n-6) and linolenic (C18:3 n-3) acid contents in polar lipids showed significant higher values in the LD and PMM muscles from pigs fed only with chestnuts. Also, the inclusion of chestnuts in the diet significantly affected the palmitic (C16:0), stearic (C18:0) and oleic (C18:1 n-9) acid contents in both lipid classes in liver; the arachidonic (C20:4 n-6) and linolenic (C18:3 n-3) acids contents were also affected in NL and PL, respectively.
7. International Symposium on the Mediterranean Pig, 2010/10/14-16, Córdoba (Spain)